Cutaneous sarcoid reaction in a case of acute lymphoblastic leukemia - Shery Mounir William Labib; Marina Mounir William Labib (Wolters Kluwer Medknow Publications, 2018)
Sarcoid reactions are noncaseating granulomas that simulate sarcoidosis. Since they do not fulfill the rest of criteria to diagnose systemic sarcoidosis, they have a separate identity. They are often reported in draining lymph nodes of malignancies. However, they can also occur in the skin forming "Cutaneous sarcoid reaction" - such as this case. We report the case of a 17-year-old female with itchy, papules persistent for 3 months while she had no other complaint. The papules were present on the trunk and lower extremities. General examination was unremarkable except for cervical lymphadenopathy. Bone marrow aspirate and biopsy revealed features of "acute lymphoblastic leukemia (ALL)". As the peripheral blood smear showed no blasts, it was hard to diagnose her leukemia. Skin biopsy showed features of granulomatous reaction simulating sarcoidosis. Her final diagnosis was compatible with "aleukemia form of ALL". The patient was started on chemotherapy and her itching was relieved with treatment. The skin papules were resolved leaving behind hyperpigmentation. The link between sarcoidal reactions and malignancies still needs further research. However, cutaneous sarcoidal reactions may be the first presentation of systemic malignancy. Patients presenting with sarcoidal reactions should be investigated to exclude the associated malignancy.